Formation of an Explosively Formed Penetrator Warhead Using a Step-Shaped Charge. (21st June 2022) - Wang, Weizhan; Chen, Zhigang; Yang, Baoliang; Jing, Tong; Meng, Fangao; Zhao, Taiyong
Abstract : In this study, the formation mechanism of an explosively formed penetrator (EFP) with tail fins was analyzed. Through static denotation and dynamic flight tests, the feasibility of using a step-shaped liner during the formation of an EFP with tail fins was verified. The influences of the step depth, h, and the step angle, Φ, on the flight stability were then explored. Based on the consistency between the numerical simulation and experimental results, the influences of the step-shaped liner's spherical arc radius, number of steps, and wall thickness on the formation and flight stability of an EFP with tail fins were further studied. The results showed that a T2 copper step-shaped liner performed better than a H90 brass liner. Compared with a hemispherical liner with an equal wall thickness, the step-shaped liners resulted in EFPs with initial angular velocities and relatively better flight stability. Moreover, a greater initial angular velocity led to a higher EFP landing accuracy.